2012
DOI: 10.1080/17450128.2012.656733
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of HIV diagnosis to HIV-infected children in South Africa: Focus groups for intervention development

Abstract: Worldwide about 2.5 million children younger than 15 years of age are living with HIV, and more than 2.3 million of them live in sub-Saharan Africa. Antiretroviral therapy has reduced mortality among HIV-infected children, and as they survive into adolescence, disclosing to them their diagnosis has emerged as a difficult issue, with many adolescents unaware of their diagnosis. There is a need to build an empirical foundation for strategies to appropriately inform infected children of their diagnosis, particula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(138 citation statements)
references
References 19 publications
21
117
0
Order By: Relevance
“…Despite parents" resistance and urge to delay full disclosure to their children, both HIV-positive and negative children reported wanting to receive full disclosure in a timely manner. Prior researchers have reported that disclosure to children is the right thing to do and the right of the child (Heeren et al, 2012;Pilowsky et al, 2000;Weiner et al, 1998); the children in this study seem to ask for it.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Despite parents" resistance and urge to delay full disclosure to their children, both HIV-positive and negative children reported wanting to receive full disclosure in a timely manner. Prior researchers have reported that disclosure to children is the right thing to do and the right of the child (Heeren et al, 2012;Pilowsky et al, 2000;Weiner et al, 1998); the children in this study seem to ask for it.…”
Section: Discussionmentioning
confidence: 48%
“…Overall, parents appear to favor disclosure at their own time without prompting from HCPs; they did acknowledge needing guidance in the process. Parents have reported requiring guidance during disclosure preparation (Heeren et al, 2012;Nam et al, 2009;Nostlinger et al, 2004;Oberdorfer et al, 2006;Rwemisisi et al, 2008;Vallerand et al, 2005;Vaz et al, 2010;Vaz et al, 2008). Prior researchers have called for discussions to occur between HCPs and parents to resolve differences that occur when…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations